Peptide Map Comparison of Infectious Pancreatic Necrosis Virus-Specific Polypeptides - Dobos, Peter (1977)
An investigation of virus-specific protein synthesis in infectious pancreatic necrosis virus (IPNV)-infected rainbow trout gonad cells was undertaken to find a relationship between the coding capacity of the virus genome (two segments of double-stranded RNA of 2.5 × 10(6) and 2.3 × 10(6) molecular weight) and the sizes and relative amounts of virus-specific proteins. Using polyacrylamide slabgel electrophoresis and autoradiography, eight distinct virus-specific polypeptides were detected in infected, [(35)S]methionine-labeled cells. These proteins may be grouped into three size classes on the basis of molecular weight: (i) large, α (90,000); (ii) medium, β(1) (59,000), β(2) (58,000), and β(3) (57,000); and (iii) small, γ(1) (29,000), γ(1A) (28,000), γ(2) (27,000), and γ(3) (25,000). The combined molecular weight of these polypetides (373,000) is beyond the coding capacity of the virus genome. Purified IPNV contained polypeptides α, β(3), γ(1), and γ(1A). Pulse-chase experiments and tryptic peptide map comparisons revealed that only four of the eight intracellular proteins were primary gene products, namely, α, β(1), γ(1), and β(2), with a combined molecular weight of 205,000. Of these primary gene products only the α polypeptide was found to be stable, whereas the other three underwent intracellular proteolytic cleavage during virus morphogenesis. Polypeptide β(1) was cleaved to generate β(2) and β(3); γ(1) was trimmed to produce γ(1A), and the only nonstructural primary gene product, γ(2), was found to be a precursor of γ(3). These results suggest that IPNV possesses a unique mechanism to synthesize three size classes of proteins using mRNA transcripts from two high-molecular-weight double-stranded RNA genome segments.